Outcome of minimal invasive surgery approach for spine infection: a systematic review - Ridia, Ketut Gede Mulyadi (International Journal of Research in Medical Sciences, 2019)
The concept of minimally invasive surgery has gained increasing popularity in the last several decades, are being introduced as an alternative to limit the surgical complications while achieving best possible outcome. While minimally invasive spine surgery holds promise for lower blood loss, faster patient recovery, shorter hospital stays, and the potential to transition procedures to the ambulatory setting, safety in spinal surgery remains paramount and has (appropriately) tempered some of the enthusiasm for the results of aggressive early adapters. Until now, there has been no literature summarizing the evidence of MIS outcome in treating spondylitis TB of the bone. The purpose of this systematic review was to investigate the outcome of minimal invasive surgery approach for spine infection. authors comprehensively searched PubMed, EMBASE, and Cochrane Library to search for studies about minimally invasive surgery as management of tuberculous spondylitis up to June 7th, 2019. The selection of appropriate studies was performed by independent investigators based on PRISMA guideline. Given the limited number of studies, there was no restriction in terms of patient’s demographics, the specific minimal invasive surgical method, and publication status. Authors identified the method for minimally invasive approach and open approach, the functional outcome, intraoperative outcome, radiological outcome, length of stay, follow up period, and complication. Authors found 81 articles from database. After evaluating full text, 8 articles (346 patients) were found to be eligible. More than 110 patients were treated with open spine surgery, while more than 270 patients were treated using minimally invasive spine surgery the minimal invasive methods were posterior pedicle screws fixation, plate fixation, lateral nail bar fixation, and bilateral pedicle screw fixation. The visualization methods include C-arm fluoroscopy, X-ray fluoroscopy. The follow-up period ranges from 1 to 40 months. The functional outcome were found to be satisfying with minimal complications. MIS yielded satisfactory result in comparison to conventional open surgery for spine infection. More long term future studies should be conducted to in order to search for more solid evidence regarding this claim.